2012
DOI: 10.1002/ana.23591
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status predicts new brain magnetic resonance imaging activity in multiple sclerosis

Abstract: Objective We sought to determine if vitamin D status is associated with developing new T2 lesions or contrast-enhancing lesions on brain MRI in relapsing multiple sclerosis (MS). Methods EPIC is a five-year longitudinal MS cohort study at the University of California, San Francisco. Participants had clinical evaluations, brain MRI, and blood draws annually. From the overall cohort, we evaluated patients with clinically isolated syndrome or relapsing-remitting MS at baseline. In univariate and multivariate (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(191 citation statements)
references
References 29 publications
8
179
0
4
Order By: Relevance
“…• A longitudinal cohort study of 469 subjects with MS found that vitamin D levels were inversely associated with the risk of new T2-weighted or gadolinium-enhancing T1-weighted lesions on brain MRI [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• A longitudinal cohort study of 469 subjects with MS found that vitamin D levels were inversely associated with the risk of new T2-weighted or gadolinium-enhancing T1-weighted lesions on brain MRI [13].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found an inverse relationship between sun exposure, ultraviolet radiation exposure, or serum vitamin D levels, and the risk or prevalence of MS [7]- [12], while others have shown that serum vitamin D levels are inversely related to MS disease activity [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…During relapses, serum 25(OH)D levels appeared to be lower, 71 and lower serum 25(OH)D levels have also been associated with an increased risk of relapses (Muris et al unpublished data) and new lesions on MRI. [79][80][81] A 50 nmol/l increase in 25(OH)D level has been calculated to result in a decrease in the relapse rate of 41-55%. 80,82 Furthermore, inverse correlations between 25(OH)D levels and the level of disability have been found.…”
Section: The D In Development and Disease Coursementioning
confidence: 99%
“…Higher levels of circulating 25-hydroxyvitamin D 3 have been recently shown to correlate with a reduction in the number of new T2 and gadoliniumenhancing lesions (3). Moreover, the bioactive form of vitamin D, 1,25-dihydroxyvitamin D 3 [1,25(OH) 2 D 3 ], can completely prevent and treat established experimental autoimmune encephalomyelitis (EAE) (4), a murine MS model. Nonetheless, the mechanism of 1,25(OH) 2 D 3 ' s in vivo action remains incompletely understood.…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Demyelinatingmentioning
confidence: 99%